Effect of immunostimulation with bacterial lysate on the clinical course of allergic rhinitis and the level of γδT, iNKT and cytotoxic T cells in children sensitized to grass pollen allergens: A randomized controlled trial - Janeczek, Kamil; Kowalska, Wioleta; Zarobkiewicz, Michał; Suszczyk, Dorota; Mikołajczyk, Marek; Markut-Miotła, Ewa; Morawska-Michalska, Izabela; Bakiera, Adrian; Tomczak, Aleksandra; Kaczyńska, Agnieszka; Emeryk, Andrzej; Roliński, Jacek; et al. (Frontiers in Immunology, 2023)
Background There are many drugs for allergic rhinitis (AR), however, these drugs show variable clinical effectiveness and some side effects. Therefore, new methods of AR pharmacotherapy are being sought. Objectives The objectives of this study were to evaluate the efficacy of polyvalent mechanical bacterial lysate (PMBL) therapy in improving the clinical course of grass pollen-induced AR (seasonal AR, SAR) in children and its effect on changes in the blood level of the γδT, iNKT and cytotoxic T cell subsets. Methods Fifty children with SAR were enrolled in this study and were randomly assigned to either the PMBL group or the placebo group. The severity of SAR symptoms was assessed using the total nasal symptom score (TNSS) and visual analogue scale (VAS). During two visits (V1, V2), peak nasal inspiratory flow (PNIF) was measured and peripheral blood was collected for immunological analyses. The study also included 2 telephone contacts (TC1, TC2). Results The severity of the nasal symptoms of SAR on the TNSS scale was revealed to have a significantly lower impact in the PMBL group vs the placebo group at measuring points TC1 and V2 (p = 0.01, p = 0.009, respectively). A statistically significantly lower mean severity of nasal symptoms of SAR on the VAS scale was recorded for children in the PMBL group compared to the placebo group at measuring points TC1, V2 and TC2 (p = 0.04, p = 0.04, p = 0.03, respectively). The compared groups do not show significant differences in terms of PNIF values at individual measuring points. There were no statistically significant changes in immune variables. For both groups, there was a statistically significant association between the level of Th1-like γδT cells and the severity of SAR symptoms expressed on the TNSS scale (p = 0.03) – the lower the level of Th1-like γδT cells, the higher the TNSS value. Conclusion Administration of sublingual PMBL tablets during the grass pollen season proves to have a high efficacy in alleviating SAR symptoms in children sensitized to grass pollen allergens. Th1-like γδT cells may be used as potential markers for SAR severity in children.